Dvojnici bolnica - bolnišnica v 19. stoletju in danes - Ulčnik, Natalija (Slavistična revija, 2014)
The present article presents diachronic and synchronic aspects of the occurrence of the competing terms bolnica - bolnišnica. We checked the occurrence of the terms in Slovene dictionaries (1781-2012); their normative use in Slovene grammars (1899-2001); their occurrence in nineteenth-century professional, literary, and journalistic works; and in the corpus of the contemporary Slovene language. We discovered that from the first half of the nineteenth century until today, both terms occur in dictionaries and literary works; however, with time the use of the terms split into a literal (bolnišnica) and non-literal (bolnica) under the influence of puritanical tendencies. We also discovered that up to the present, normative reference works did not take into account the terms' stability in various professional fields, as illustrated by such distinctive phrases as splošna bolnišnica - veterinarska bolnica.
Keywords: besedilna raba; knjižni jezik; slavisms; slavizmi; Slovene; Slovene language; slovenščina; standard language; standard language norm; word use